Pre-course Apprenticeship for B Lib SC - Neelameghan, A.; Bhattacharyya, G. (Journal of Information and Knowledge, 1966)
Points out the need for a Pre-course Apprenticeship as a preparatory period for the Formal Course, enumerates its objectives, considers the factors involved in the overall as well as detailed planning for it. Gives a proforma of the Instruction Sheet and of the Diary to be used in the Apprenticeship Course.